The Gradualism of Cultural Resurgence of Afro-Arabic in the Shadow of Civilization (Journal of International Studies, 2017)
Intellectual vitality of the Arabic culture came into stagnation through the close of the 18th century. However, the beginning of the 19th century potrayed the rebirth of the Arabic culture seen first in Lebanon, Syria and Egypt, from where it spread gradually in varying degrees to other parts of the Arab world. This cultural resurgence with its full import of the Arab Muslim society especially in Africa has prompted the rise in Arab national consciousness (nationalism) as well as religious (Islamic) reawakening, which have a wonderful over effect on the contemporary World Order. The methodology adopted in this paper was document review. This paper tried to investigate the gradual process of the Arabic cultural resurgence, which has found expression in the shifting paradigm of Arabic literary works of some literati and religious revivalism in Africa. In fact, it is noticed that Arabism has been an integral part of Islam; the activities of the nationalist movement and that of Islamic reformers have political and cultural consequences in the modern world.